The Influence of Emotional Intelligence on Employee Satisfaction in Islamic State University Syarif Hidayatullah Jakarta - Siti Nurhasanah; Elvira Sitna Hajar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to determine the direct and indirect effect of variables on emotional intelligence, leadership, work motivation on job satisfaction of employees at the Faculty of Economics and Business, Syarif Hidayatullah State Islamic University, Jakarta. The research method used is quantitative through a survey with a causal approach which will be analyzed using path analysis. The sample frame in this study amounted to 85 people. The sampling method used is simple random sampling, which is 30 employees as the sample. Based on the results of the research, the emotional intelligence variable with employee job satisfaction, the emotional intelligence variable with leadership, the work motivation variable with employee job satisfaction is accepted, that is, there is no direct influence. And for the variable of work motivation with leadership and the variable of leadership with job satisfaction of employees at FEB UIN Syarif Hidayatullah Jakarta has a direct influence